A report on the practice in industry training in fish capture. - Lacuesta, Rodolfo M. (College of Fisheries, University of the Philippines, 1960)
Fishing is one of the most important industries of the Philippines. In fact, it ranks second to the agriculture both the value of the product and the number of individuals engaged in and benefited by it. So the government is doing its part in promoting the fishing industry of the country. Research in fisheries is being conducted in order to increase production and conserve the natural resources of the sea. Methods of fishing are being developed, likewise techniques of fishing is modified. In this case fishing development ids being kept up in order to meet the needs of the people to supplement fish production of the country. This report describes ways and methods of fishing, which I came across in the course of four months of continuous and intensive practice-in-industry training. When I undertook my apprenticeship as an observer and as a working student, my main aim was not only to comply with the requirements alone but also to contribute little knowledge that I could gather to my fellow students in particular and to the country in general. I tried my best to fill up the necessary information needed although the time allotted for the preparation of this report is rather short. While on the field, because of the fact that specialization in any gear is impossible, concentration was largely focused on the construction, method of operation and in gathering pertinent data regarding the gear. In most cases data were difficult to secure for fear of competition perhaps, however, the data presented herein can still be regarded reliable information as they were taken from the average cases. This report though brief and concise, is the result of the author's attempt to contribute a little knowledge to young people of the coming generation. So I do hope that this compilation, though short it may be, can serve as a source of local information.